We were heroes 1st cavalry division (airmobile) Vietnam - Rasen Jr. Edward J. (Canada : Madacy Video, 2002)
Collection story of 1st cavalry division (airmobile), one of the most famous and most decorated combat divisions of the United States Army on Vietnam War
First team in Vietnam -- Know your enemy: the Viet Cong -- The airmobile division -- Army air-mobility team -- Progress to peace -- First cavalry division (Airmobile) in Vietnam -- U.S. army helicopter operation in Vietnam -- Logistics in Vietnam (Pipeline to victory)
Title from title screen
DVD format
Dolby digital
With optional subtitles on English, Chinese or Bahasa
Keywords: United States. -- Army. -- Air Cavalry Division, 1st; Vietnamese Conflict, 1961-1975 -- Aerial operations, American; Vietnamese Conflict, 1961-1975 -- Campaigns; Vietnam War, 1961-1975 -- Regimental histories -- United States